Management control in an area of the NCB: Rationales of accounting practices in a public enterprise - Berry, A.J.; Capps, T.; Cooper, D.; Ferguson, P.; Hopper, T.; Lowe, E.A. (Accounting, Organizations and Society, 1985)
This paper explores the rationales offered by participants for the accounting and management control practices in which they are involved. An analysis of these rationales emphasis four characteristics of current practices. Firstly, financial planning and control systems do not appear to be a dominant mode of organisational control for the organisation investigated, physical production planning appearing to be more important. Secondly, the parts of the whole organisation appear to be only loosely coupled, thereby insulating the various parts from each other, and from pressures for change. Thirdly, in such a context, accounting and information generally may be managed either (or both) to enhance ambiguity or to provide legitimacy in (and about) the organisation. The paper concludes, fourthly, by noting the pressures for change which appear to operate through the finance function, thereby enhancing that function's organisational role. The observations and analysis of the paper are based on an in-depth observational study of an Area (i.e. geographical division) of the National Coal Board, in the U.K., and on a detailed study of that organisation's history and environment.